Effect of Mild and Moderate Hepatic Impairment (Defined by Child–Pugh Classification and National Cancer Institute Organ Dysfunction Working Group Criteria) on Pexidartinib Pharmacokinetics. (31st March 2022) - Zahir, Hamim; Greenberg, Jonathan; Hsu, Ching; Marbury, Thomas C.; Lasseter, Kenneth C.; Xu, Li‐An; Tap, William D.; Healey, John H.; Stacchiotti, Silvia; LaCreta, Frank
Abstract: Pexidartinib is a novel oral small‐molecule tyrosine kinase inhibitor targeting the colony‐stimulating factor 1 receptor. Pexidartinib undergoes extensive hepatic metabolism via multiple cytochrome P450 and uridine 5'‐diphospho‐glucuronosyl transferase enzymes, with ZAAD‐1006a as the only major metabolite in human plasma. As pexidartinib is extensively metabolized, hepatic impairment (HI) could lead to increased exposure to pexidartinib. The objective of the two phase 1, open‐label studies was to determine the pharmacokinetics of pexidartinib after a single 200‐mg dose in subjects with mild and moderate HI, based on Child–Pugh classification (PL3397‐A‐U123: 8 mild HI and 8 moderate HI vs 16 matched healthy controls) and National Cancer Institute Organ Dysfunction Working Group (NCI‐ODWG) criteria (PL3397‐A‐U129: 8 moderate HI versus 8 matched healthy controls [NCT04223635]). Based on Child–Pugh classification, exposure to pexidartinib (maximum observed concentration [Cmax ], area under the plasma concentration–time curve up to the last measurable concentration [AUClast ], and extrapolated to infinity [AUCinf ]) was similar in subjects with mild and moderate HI and in respective matched healthy controls, whereas ZAAD‐1006a exposure (AUC) was approximately 27% to 28% and 41% to 48% higher in mild and moderate HI, respectively. According to NCI‐ODWG criteria, total pexidartinib exposure was 42% to 46% higher in subjects with moderate HI, compared with healthy controls, and total ZAAD‐1006a exposure was 70% to 79% higher for subjects with moderate HI, compared with matched healthy controls with normal hepatic function. These findings were used to develop appropriate dose recommendations in patients with hepatic impairment.